An ethnobotanical study of herbs and medicinal plants used in Western, Copperbelt, Central and Northern provinces of Zambia - James Nyirenda; Mutinta Chipuwa (Elsevier, 2024)
Background: About 70 % of the population in Zambia still depend on medicinal plants for primary health care. The limited number of published and documented information on medicinal plants in Zambia remains a challenge. Thus, the aim of this study was to compile some plants used traditionally as medicines in Western, Copperbelt, Central, and Northern Provinces of Zambia, indicating their local and botanical names, parts of the plants used, indications and dosage forms. Methods: Convenient sampling approach was used to collect data. Four (4) provinces in Zambia were conveniently selected and 10 plants for each province were identified except for Northern province where only 5 plants species were again randomly selected. Based on this criterion, a total of 35 plant species were compiled, representing 20 families. Data was mainly collected from primary sources that included elders in communities, few from available literature and none from traditional healers/herbalists. Results: The roots were the commonly used part at 38 %, followed by leaves and stem bark for most woody plants and trees. The most mentioned plant was Cassia abbreviata- Fabaceae family (Umunsokansoka) in Northern (RFC=1), followed by Kigelia Africana-Bignoniaceae family (Umufungufungu) (RFC=0.8) on the Copperbelt. Combretum hereroense-Combretaceae family (Mububu), Cassia occidentalis-Fabaceae family (Changu) from Western, while A. Spinosus, A. viridis, A. gangeticus-Amaranthaceae, Amarathus spp fmily (Bondwe) on the Copperbelt and Ficus sycomorus-Moraceae family (Mukuyu) in Central Province recorded an RCF=0.6 respectively. The Fabaceae family contributed 20 % of the plants sampled showing high use of plants from this family. Conclusions: The regions sampled shows a rich biodiversity of plants with important medicinal properties against various health conditions such as tuberculosis, diabetes, hypertension and sexually transmitted infections as well as HIV. More work needs to be done to assess quantitatively the many claims in a scientifically approved manner to assess viability of the same as complementary alternative medicines.